The Neuropharmacogenomical Perspectives of Bipolar Disorders - Anurogo, Dito (PT. Kalbe Farma Tbk., 2016)
Bipolar disorder (BD), also known as manic-depressive illness, is a brain disorder causing unusual shifts in mood, energy, activity levels, and the ability to carry out daily tasks, caused by multifactorial and enigmatic etiologies. The main objective of this overview is to review recent findings and critically evaluate BD based on neurogenomics and pharmacogenomics perspectives, through searching appropriate online database sources and relevant bibliographies. Recent studies and references explain genome-wide significant loci for bipolar disorder (polygenetics), potential biomarkers (apoptosis and neurotrophic factors, immuno-inflammatory factors, neurotrophins, BDNF, IGF-1, VEGF, etc.), dysregulationÂ of immuno-inflammatory mechanisms, the role of neuroplasticity in the pathophysiology and treatment of BD, genetic effect of lithium response in BD. Stem cells, omics technologies, and optogenetics is considered to be effective strategies to overcome BD.